Kinetic study on the production of biodegradable lubricant by enzymatic transesterification of high oleic palm oil - Wafti, Nur Sulihatimarsyila Abd; Choong, Thomas Shean Yaw; Lau, Harrison Lik Nang; Yunus, Robiah; Abd-Aziz, Suraini; Raof, Nurliyana Abdul (Elsevier, 2023)
Kinetic studies are necessary to identify inhibitors of lipase enzyme deactivation in reaction systems because varying substrate concentrations can affect the enzyme's catalytic activity. The present study aimed to analyze the reaction kinetics of palm-based polyol ester production catalyzed by commercial lipase Novozyme 435 (N435). The enzymatic transesterification reaction was performed in a solvent-free medium. The effect of substrates concentration, specifically high oleic palm methyl ester (HO-PME) and trimethylolpropane (TMP), on the kinetic constant was studied at the initial reaction rate. The study was conducted based on the Ping-pong Bi-bi model, assuming that both substrates could inhibit the reaction. The reaction was carried out at 70 °C and 15.25 mbar with a 3 % (w/w) N435 enzyme load to investigate the effect of various HO-PME and TMP concentrations. The kinetic constants obtained are as follows: Km(HOPME) = 61.112 mol/L, Km(TMP) = 0.336 mol/L, Ki(HOPME)= 0.002 mol/L, Ki(TMP) = 2.415 mol/L and Vmax = 17.24 mol/L.hr. The results implied that N435 has higher affinity towards TMP than HO-PME. Inhibition constant indicated a lower inhibitory function of the TMP than HO-PME (Ki(TMP) >Ki(HOPME)). The reaction kinetics obtained in this study agreed well with the model used with TMP and HO-PME as competitive inhibitor during enzymatic transesterification.